The Impact of Ramadan Fasting on Glycemic Control in Patients with Type 2 Diabetes : A Comprehensive Systematic Review - Gusti Arlan Tio; Ramadilla (International Medical Journal Corp. Ltd, 2026)
Introduction: Ramadan fasting is observed by millions of Muslims with type 2 diabetes mellitus (T2DM) worldwide, presenting unique challenges for glycemic management. This systematic review synthesizes evidence on the impact of Ramadan fasting on glycemic control in patients with T2DM. Methods: A comprehensive systematic review was conducted including 80 studies (35 randomized controlled trials and 45 observational studies) examining Ramadan fasting in adults with T2DM. Studies were included if they assessed glycemic parameters (HbA1c, fasting blood glucose, postprandial glucose, glucose variability) and reported safety outcomes. Data were extracted on study characteristics, medication regimens, educational interventions, and metabolic outcomes. Results: The majority of studies demonstrated improvements or stability in HbA1c levels during Ramadan, with reductions ranging from 0.5-1.5% in patients receiving structured interventions. Newer medication classes including SGLT-2 inhibitors (HbA1c reduction 0.49-0.65%), GLP-1 receptor agonists (mean difference -0.31%, p=0.04), and DPP-4 inhibitors showed favorable safety-efficacy profiles. Hypoglycemia rates varied considerably: sulfonylureas 14-26%, insulin 2-23%, DPP-4 inhibitors 0-5.8%, SGLT-2 inhibitors 0.3-7.3%, and GLP-1RAs 0-5%. Structured pre-Ramadan education reduced hypoglycemia from 19.5% to 4.1% and improved HbA1c by 0.7-1.5%. Dose reduction protocols (60% of usual dose) decreased hypoglycemia from 23.0% to 4.2% (OR 0.15, 95% CI 0.08-0.26). Weight changes ranged from -2.9 kg to no significant change, with SGLT-2 inhibitors and GLP-1RAs producing greatest reductions. Discussion: Ramadan fasting can be safe for many T2DM patients with appropriate risk stratification, medication adjustment, and structured education. Newer glucose-lowering agents offer superior safety profiles compared to sulfonylureas and traditional insulin regimens. Conclusion: Successful Ramadan fasting requires individualized approaches combining pre-Ramadan education, medication optimization, structured nutrition therapy, and appropriate monitoring. High-risk patients should be advised against fasting.